Cortical generation of on-going "Delta" and "Alpha" EEG rhythms in mouse models of Alzheimer's disease and Alzheimer's disease patients at prodromic stages. Issue 3 (March 2016) - Babiloni, C.; Del Percio, C.; Marzano, N.; Cordone, S.; Noce, G.; Bagnoli, C.; Rossini, P. Maria; Soricelli, A.; Nobili, F. Mariano; Faz, D. Bartres; Blin, O.; Payoux, P.; et al.
Abstract : Background and aim: In the framework of IMI PharmaCog project (Grant Agreement n°115009, www.pharmacog.org ), this study evaluated whether cortical sources of resting state EEG rhythms were related to cerebrospinal fluid A®42 level in amnesic mild cognitive impairment (MCI) subjects and have translational value in mouse model of AD. Methods: The research data (including human biological samples) were sourced ethically and used in line with international ethical standards. EEG rhythms were recorded in 127 aMCI subjects. Cortical sources of global delta (2–4 Hz) and low-frequency alpha (8–10.5 Hz) EEG rhythms were estimated by LORETA package. Back translation was tested on on-going EEG rhythms in wild type and transgenic mouse models of AD developing accumulation of A®42 in the brain (i.e. PDAPP, TASTPM). Results and conclusions: (1) delta (<4 Hz) and dominant alpha frequencies (8–10 Hz) of cortical EEG rhythms were abnormal in the aMCI group in relation to positivity to A®42 in the CSF and/or disease progression, respectively; (2) EEG rhythms in the above frequency ranges were abnormal in transgenic mice (i.e. PDAPP, TASTPM) when compared to wild type ones. Resting state EEG rhythms may reflect AD amyloidosis in aMCI subjects and may have a counterpart in transgenic mouse models of AD.